KCNJ11activating mutations in Italian patients with permanent neonatal diabetes - Ornella Massa; Dario Iafusco; Elena D’Amato; Anna L. Gloyn; Andrew T. Hattersley; B Pasquino; Giuseppe Tonini; Francesco Dammacco; Giorgio Zanette; Franco Meschi; Ottavia Porzio; GianFranco Bottazzo; et al. (2004)
Permanent neonatal diabetes mellitus (PNDM) is a rare condition characterized by severe hyperglycemia constantly requiring insulin treatment from its onset. Complete deficiency of glucokinase (GCK) can cause PNDM; however, the genetic etiology is unknown in most PNDM patients. Recently, heterozygous activating mutations of KCNJ11, encoding Kir6.2, the pore forming subunit of the ATP-dependent potassium (KATP) channel of the pancreatic β-cell, were found in patients with PNDM. Closure of the KATP channel exerts a pivotal role in insulin secretion by modifying the resting membrane potential that leads to insulin exocytosis. We screened the KCNJ11 gene in 12 Italian patients with PNDM (onset within 3 months from birth) and in six patients with non-autoimmune, insulin-requiring diabetes diagnosed during the first year of life. Five different heterozygous mutations were identified: c.149G>C (p.R50P), c.175G>A (p.V59M), c.509A>G (p.K170R), c.510G>C (p.K170N), and c.601C>T (p.R201C) in eight patients with diabetes diagnosed between day 3 and 182. Mutations at Arg50 and Lys170 residues are novel. Four patients also presented with motor and/or developmental delay as previously reported. We conclude that KCNJ11 mutations are a common cause of PNDM either in isolation or associated with developmental delay. Permanent diabetes of non autoimmune origin can present up to 6 months from birth in individuals with KCNJ11 and EIF2AK3 mutations. Therefore, we suggest that the acronym PNDM be replaced with the more comprehensive permanent diabetes mellitus of infancy (PDMI), linking it to the gene product (e.g., GCK-PDMI, KCNJ11-PDMI) to avoid confusion between patients with early-onset, autoimmune type 1 diabetes. Hum Mutat 25:22–27, 2005. © 2004 Wiley-Liss, Inc.